2022
DOI: 10.1002/jmv.28386
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic reveals the ferroptosis features of host response in a mouse model of Zika virus infection

Abstract: Zika virus (ZIKV) is a neurotropic flavivirus. The outbreak of ZIKV in 2016 created a global health emergency. However, the underlying pathogenic mechanisms remain elusive. We investigated the host response features of in vivo replication in a mouse model of ZIKV infection, by performing a series of transcriptomic and bioinformatic analyses of ZIKV and mock‐infected brain tissue. Tissue damage, inflammatory cells infiltration and high viral replication were observed in the brain tissue of ZIKV infected mice. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 68 publications
(125 reference statements)
0
4
0
Order By: Relevance
“…These findings support the role of iron-induced death in Mtb-triggered necrosis. Further research revealed that the knockdown of heme oxygenase 1 (Hmox1) by siRNA resulted in a diminution of antioxidant factors GPX4 and FSP1 [ 32 ], along with an increased release of intracellular bacteria in Bacillus Calmette-Guérin (BCG)-infected macrophages [ 743 ]. These observations suggest that Mtb propagation occurs through ferroptosis, thereby inspiring us to search for promising strategies to manage pulmonary tuberculosis by focusing on ferroptosis-induced necrosis.…”
Section: Ferroptosis In Pathologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings support the role of iron-induced death in Mtb-triggered necrosis. Further research revealed that the knockdown of heme oxygenase 1 (Hmox1) by siRNA resulted in a diminution of antioxidant factors GPX4 and FSP1 [ 32 ], along with an increased release of intracellular bacteria in Bacillus Calmette-Guérin (BCG)-infected macrophages [ 743 ]. These observations suggest that Mtb propagation occurs through ferroptosis, thereby inspiring us to search for promising strategies to manage pulmonary tuberculosis by focusing on ferroptosis-induced necrosis.…”
Section: Ferroptosis In Pathologiesmentioning
confidence: 99%
“…Due to involving various and complicated signaling, ferroptosis plays an important role in the occurrence and development of major chronic diseases and different roles in different disease contexts. A growing body of evidence suggests that the imbalance of ferroptosis affects, development and aging [ 13 , 14 ], and is closely related to the tumor [ 8 , 15 , 16 ], ischemic diseases [ 17 22 ], neurodegenerative disease [ 23 , 24 ], organ transplantation [ 25 , 26 ], cardiovascular disease [ 27 29 ], autoimmune functions [ 15 , 30 ], infection [ 31 , 32 ], iron-overload disease [ 33 ], and so on (Fig. 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Newcastle disease virus (NDV) induces GPX4-dependent ferroptosis by activating p53 ( Kan et al., 2021 ). Although a recent study using RNA-seq has demonstrated that ferroptosis-related pathways are significantly activated in ZIKV-infected mouse brains ( Yan et al., 2023 ), there is still no clear evidence on whether ferroptosis is involved in the pathogenesis of flaviviruses.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, aberrantly expressed SAT1 is closely related to cancer development, including LUAD 10 , 12 . Recently, SAT1 was reported to be associated with the regulating process of ferroptosis in tumor cells 11 , 13 . However, the mechanism by which cancer regulates SAT1 to affect ferroptosis is still unidentified.…”
Section: Introductionmentioning
confidence: 99%